Genistein and Glyceollin Effects on ABCC2 (MRP2) and ABCG2 (BCRP) in Caco-2 Cells - Schexnayder, Chandler; Stratford, Robert (International journal of environmental research and public health, 2015)
The goal of the present study was to determine the effects of glyceollins on intestinal ABCC2 (ATP Binding Cassette C2, multidrug resistance protein 2, MRP2) and ABCG2 (ATP Binding Cassette G2, breast cancer resistance protein, BCRP) function using the Caco-2 cell intestinal epithelial cell model. Glyceollins are soy-derived phytoestrogens that demonstrate anti-proliferative activity in several sources of cancer cells. 5 (and 6)-carboxy-2′,7′-dichloroflourescein (CDF) was used as a prototypical MRP2 substrate; whereas BODIPY-prazosin provided an indication of BCRP function. Comparison studies were conducted with genistein. Glyceollins were shown to inhibit MRP2-mediated CDF transport, with activity similar to the MRP2 inhibitor, MK-571. They also demonstrated concentration-dependent inhibition BCRP-mediated efflux of BODIPY-prazosin, with a potency similar to that of the recognized BCRP inhibitor, Ko143. In contrast, genistein did not appear to alter MRP2 activity and even provided a modest increase in BCRP efflux of BODIPY-prazosin. In particular, glyceollin inhibition of these two important intestinal efflux transporters suggests the potential for glyceollin to alter the absorption of other phytochemicals with which it might be co-administered as a dietary supplement, as well as alteration of the absorption of pharmaceuticals that may be administered concomitantly.